SURGICAL SITE INFECTION IN LUMBAR SURGERIES, PRE AND POSTOPERATIVE ANTIBIOTICS AND LENGTH OF STAY: A CASE STUDY - Khan, Inayat Ullah; Janjua, Muhammad Burhanuddin; Hasan, Shumaila; Shah, Shahid (Journal of Ayub Medical College Abbottabad, 2009)
Background: Postoperative wound infection also called as surgical site infection (SSI), is a trouble some complication of lumbar spine surgeries and they can be associated with serious morbidities, mortalities and increase resource utilization. With the improvement in diagnostic modalities, proper surgical techniques, antibiotic therapy and postoperative care, infectious complications can result in various compromises afterwards. The objective was to study the relation of surgical site infection in clean lumbar surgeries with the doses of antibiotics. This Retrospective study was conducted at Shifa International Hospital, from January 2006 to March 2008. Methods: Hundred post operated cases of lumber disc prolapse, lumbar stenosis or both studied retrospectively by tracing their operated data from hospital record section for the development of surgical site infection (SSI). The patients were divided into three groups depending upon whether they received single, three or more than three doses of antibiotics respectively. Complete data analyses and cross tabulation done with SPSS version 16. Result: Of 100 cases, only 6% had superficial surgical site infection; only 1 case with co morbidity of hypertension was detected. Twenty-one cases had single dose of antibiotic (Group-I), 59 cases had 3 doses (Group-II) and 20 cases received multiple doses (Group-III). There was no infection in Group-I. Only one patient in Group-II and 5 patients in Group-III developed superficial SSI. While 4 in Group-II, 3 in Group-III, and none of Group-I had >6 days length of stay (LOS). Conclusion The dose of antibiotic directly correlates with the surgical site infection in clean lumbar surgeries. When compared with multiple doses of antibiotics a single preoperative shot of antibiotic is equally effective for patients with SSI. Keywords: Lumber surgery, surgical site infection, wound infection